2019
DOI: 10.1002/cl2.1017
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐first century adaptive teaching and individualized learning operationalized as specific blends of student‐centered instructional events: A systematic review and meta‐analysis

Abstract: Teacher's role: Ranging from authority figure and sole source of information, to teacher as equal partner in the learning process.Adaptability: Degrees of manipulating learning environments, materials, and activities to make them more student-centered. | What is this review about?Teaching in K-12 classrooms involves many decisions about the appropriateness of methods and materials that both provide content and encourage learning.This review assesses the overall impact on student achievement of processes and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 318 publications
0
17
0
Order By: Relevance
“…Data were synthesized using a meta-analytic method based on a random effects model due to the small studies even though the results of heterogeneity testing for the studies were not significant (Q(20) = 27.499, I 2 =27.269, p > 0.05) [7]. All effect sizes were changed to the Hedges g statistic because it contains a small sample bias correction [34, 35]. Sensitivity analysis is an analytical method that examines how results change according to the criteria and contents of analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Data were synthesized using a meta-analytic method based on a random effects model due to the small studies even though the results of heterogeneity testing for the studies were not significant (Q(20) = 27.499, I 2 =27.269, p > 0.05) [7]. All effect sizes were changed to the Hedges g statistic because it contains a small sample bias correction [34, 35]. Sensitivity analysis is an analytical method that examines how results change according to the criteria and contents of analysis.…”
Section: Methodsmentioning
confidence: 99%
“…28 Adaptive individualized learning paths have been shown to substantially reduce time to proficiency and increase ultimate outcome performance, perhaps by as much as one to two standard deviations. 29,30,31 These gains are robust, as a metaanalysis of adaptive instruction studies demonstrated positive effect sizes that vary between 0.20 and 1.05, 32 with an aggregate estimate across studies of ~0.65 (Goldberg 33 found a similar aggregate effect size, 0.60; Bernard 34 found a bit lower aggregate effect size, 0.44). Thus, if XR training solutions are designed as a continuum, and content adapts according to proficiency, the combined effect sizes are expected to be well within or beyond the ''zone of desired effects'' ( > 0.4 8 ).…”
Section: Types Of Adaptationmentioning
confidence: 94%
“…These expected gains are comparable to highly lauded human tutoring, which metaanalyses of effect sizes have shown to vary from about 0.20-0.80. [34][35][36] Adaptive XR training solutions could thus play a critical role in assisting the military medical community and beyond in meeting their growing training demands.…”
Section: Types Of Adaptationmentioning
confidence: 99%
“…We calculated the effect size as Hedges’s g, not as Cohen’s d, as the latter may be overestimated when the sample size is small 42 , and most selected single studies had small sample sizes. The weight of the effect size was calculated as the inverse of the variance.…”
Section: Methodsmentioning
confidence: 99%